2021
DOI: 10.17582/journal.pjar/2021/34.1.128.135
|View full text |Cite
|
Sign up to set email alerts
|

Apposite Sowing Techniques to Optimize Productivity and Profitability of Berseem

Abstract: Huge deficit in demand and domestic production of green fodder exists that need to be abridged to cope with demand of fast-growing livestock sector. Livestock being an essentials agriculture allied sector shares around 11 % in GDP, which is 60.54 % of agriculture contribution to GDP (GoP, 2019). Due to shortage as well as unavailability of good quality Abstract | Berseem (Trifolium alexandrinum L.) is an important fodder crop of Pakistan that provides nutritious and palatable fodder in repeated cuttings. Gap i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…From the results of experiment, broadcasting method produced significantly higher morphological and yield related traits than the row sowing method with different spacing. (Gondal et al, 2021b;Gaballah, 2006) also reported similar results. It is noticed that broadcast method produced taller plants compared with row sowing method of berseem crop.…”
Section: Seed Yieldsupporting
confidence: 62%
See 2 more Smart Citations
“…From the results of experiment, broadcasting method produced significantly higher morphological and yield related traits than the row sowing method with different spacing. (Gondal et al, 2021b;Gaballah, 2006) also reported similar results. It is noticed that broadcast method produced taller plants compared with row sowing method of berseem crop.…”
Section: Seed Yieldsupporting
confidence: 62%
“…These consequences are similar with the conclusions of (Gaballah, 2006), who described that broadcast method produced heavier thousand grain weigh than the row spacing methods. Moreover, (Gondal et al, 2021b) also reported that broadcast method had significant effect 1000-grain weight as compared to row spacing one. (Gondal et al, 2021b;Gaballah, 2006;Arora et al, 1998) also described similar results and found that broadcast method produced significantly higher seed yield than the row sowing method.…”
Section: Seed Yieldmentioning
confidence: 93%
See 1 more Smart Citation
“…These results are similar to previous investigations of several scientists. This might be owing to proper aeration, nutrient, and water uptake (Khan et al, 2012;Gondal et al, 2021).…”
Section: Treatmentsmentioning
confidence: 99%
“…Although forage dearth is reported around the year, but during November-December and May-June, it becomes more obvious. Due to deficit as well as the inaccessibility of quality forage, livestock keeps on underfed with less production (Gondal et al, 2021). Farmer's unawareness of improved cultivars and less adaptation to the latest production technologies of fodder crops are major restrictions on low production of forage in Pakistan (Fodder Research Institute, 2018).…”
Section: Introductionmentioning
confidence: 99%